Effect of composite cored wire composition on the inclusions in 38CrMoAl high aluminum steel - Bingshan Wang; Shuo Zhao; Huayu Wen; Jianfeng Wang; Xiaolin Sun; Gaoyang Song; Shengping He; Zushu Li (Journal of Materials Research and Technology)
The modification and removal effect of inclusions with traditional calcium treatment in high Al steel are not ideal and the production cost is high, the effects of different types, compositions and utilization rates of cored wire on the morphology of inclusions in 38CrMoAl high Al steel are investigated to solve this problem. It is found that feeding the composite cored wire can have a better effect on the modification of inclusions in 38CrMoAl steel. The following conclusions are obtained: The inclusions in the steel after composite cored wire feeding treatment are mainly CaO-Al2O3-MgO inclusions. Compared with the untreated steel samples, the T.[O] content in the steel samples treated with composite calcium aluminate cored wire, composite calcium cored wire and pure calcium cored wire decreased by 13.94 ppm, 12.5 ppm and 10.5 ppm on average, the size of inclusions decreased by 2.72 μm, 2.78 μm and 2.68 μm on average, and the number of inclusions decreased by 19.29 %, 11.73 % and 9.88 % on average. Compared with the calcium cored wire treatment, the CaS content in the steel sample treated with the composite cored wire was significantly reduced, and the CaO content was significantly increased. Under the condition of Ca yield of 20 %, the composite calcium aluminate cored wire with calcium aluminate accounted for 80 % has the best treatment effect. The liquid inclusions with low melting point in molten steel account for 70 %, the lowest T.[O] content is 3 ppm, and the lowest number of inclusions per unit area is 55/mm2.